Economic Efficiency of the Maize Grain - Ana-Mariana Dincu; Ioan Brad; Tiberiu Iancu; Remus Gherman; Ramona Ciolac; Flavia Lupulescu (Scientific Papers Animal Science and Biotechnologies, 2023)
In this work, was calculated and the level of profitability for several levels of production for grain maize cultivation.